The swimming drill book. - Guzman, Ruben, ....- (Champaign : Human Kinetics, 2007)
Improve your times by improving your technique! Whether you are a competitive swimmer, coach, triathlete, or dedicated fitness enthusiast, The Swimming Drill Book will propel you to better results by maximizing efficiency in the water. With 128 highly effective drills, expert instruction, and more than 375 detailed illustrations, you can use this comprehensive resource to improve every facet of your swimming. Establish a greater sense of balance and position in the water; maintain perfect form for the freestyle, backstroke, breaststroke, and butterfly; and master the techniques for starts, turns, and finishes. Use the drills individually or create a personalized program based on your goals and fitness level. Either way, the tools you need are within your grasp.
Inhoudsopgave : Chapter 1. Body Position and Buoyancy Chapter 2. Breathing and Kicking Chapter 3. Sculling Chapter 4. Backstroke Chapter 5. Freestyle Chapter 6. Breaststroke Chapter 7. Butterfly Chapter 8. Freestyle and Backstroke Turns Chapter 9. Other Turns and Finishes Chapter 10. Starts
Keywords: Zwemmen